Food habit of the adolescents in relation with socio-demographic variables in a selected high school in Khulna City - Paroi, Silvia; Islam, ABM Ariful; Hasanat, Md Abul; Zohora, Fatema Tuj (Mediscope, 2020)
Background: The actions, reactions, and thoughts of an individual are influenced by other people or groups. Factors influencing food choice are not only based upon individual preferences, but are constrained by circumstances that are social (such as peer pressure), cultural and economic. Objectives:To find out the relation of adolescent’s food habit with their socio-demographical condition. Methods: This was a cross-sectional type of descriptive study which was carried out among the students of Rev. Paul’s high school, Gallamari, Khulna city with a view to assess the relation of adolescent’s food habit with their socio-demographical condition. The sample size was 217 which were selected by systematic sampling method from adolescent (10 year-16 year) students of that school. Data was collected according to a partially structured questionnaire by face to face interview administered by interviewer. The frequency distributions of the entire variables were checked by using SPSS 16.0 windows program. Chi-square test was applied to find out the association between food habits of adolescents with the socio-demographic variables. Results: In this study it was found that only 21.7% of respondents have snacking (fast food/dairy food) behaviour at least three times per week. Among 217 of the respondents, 116 (53.5%) were girls and 107 (49.3%) were in between 13yr-14yr of age. There was no statistically significant positive relation in gender and age of respondents with eating habits. Among the respondents, 60 (27.6%) fell into upper income group, out of them 25 (41.7%) respondents likes to eat fast food/dairy food. Again 32(39.5%) out of total 81 (37.3%) respondents whose mothers worked outside of home liked to eat fast food/dairy food. The test revealed that there was statistically significant positive relation between economic condition and mother’s occupation of respondents with their eating habits. It was found that 120 (55.3%) had peer influence on their food choice. The study result statistically suggested that the more an adolescent is influenced by peers and friends, the more unhealthy will be the adolescent’s eating habits. In summary, it would appear that peer emerged as the single best predictor of eating habits among adolescents. Conclusion: The findings of the result might be helpful for developing awareness among adolescents as well as parents and teachers regarding unhealthy behavior of adolescents to reduce the risk of unusual health outcome as well as to know about the associated factors which are related to unhealthy behavior, thus helpful to cut-off the factors from daily life style and become healthy citizen. Mediscope Vol. 7, No. 1: Jan 2020, Page 38-43